Dose-Dependent Change in Elimination Kinetics of Ethanol due to Shift of Dominant Metabolizing Enzyme from ADH 1 (Class I) to ADH 3 (Class III) in Mouse - Takeshi Haseba; Kouji Kameyama; Keiko Mashimo; Youkichi Ohno (International Journal of Hepatology)
ADH 1 and ADH 3 are major two ADH isozymes in the liver, which participate in systemic alcohol metabolism, mainly distributing in parenchymal and in sinusoidal endothelial cells of the liver, respectively. We investigated how these two ADHs contribute to the elimination kinetics of blood ethanol by administering ethanol to mice at various doses, and by measuring liver ADH activity and liver contents of both ADHs. The normalized AUC (AUC/dose) showed a concave increase with an increase in ethanol dose, inversely correlating with β. CLT (dose/AUC) linearly correlated with liver ADH activity and also with both the ADH-1 and -3 contents (mg/kg B.W.). When ADH-1 activity was calculated by multiplying ADH-1 content by its Vmax⁡/mg (4.0) and normalized by the ratio of liver ADH activity of each ethanol dose to that of the control, the theoretical ADH-1 activity decreased dose-dependently, correlating with β. On the other hand, the theoretical ADH-3 activity, which was calculated by subtracting ADH-1 activity from liver ADH activity and normalized, increased dose-dependently, correlating with the normalized AUC. These results suggested that the elimination kinetics of blood ethanol in mice was dose-dependently changed, accompanied by a shift of the dominant metabolizing enzyme from ADH 1 to ADH 3.